Diversidade de espécies de Moscas-das-frutas (Anastrepha spp.) na cultura do Araçá-boi (Eugenia stipitata mcvaugh) em duas áreas no município de Manaus-AM - Chaves, Edigelson Braz (Instituto Nacional de Pesquisas da Amazônia - INPA, 2016)
The study of species diversity of fruit flies, in of araçá-boi, is important to the understanding of insect/plant interactions and to characterize the community of insects in the Amazon ecosystem. The objective of this work was to determine the species diversity of fruit flies, population fluctuation, faunistic analysis, level of infestation and parasitoids of fruit flies in crops of araçá-boi in two orchards, in IFAM Campus-East Zone and Mini Campus of UFAM in Manaus-AM, in the period of June 2015 to May 2016. The captures of insects/fruit flies were carried out with McPhail traps, whose bait was 300 ml of hydrolysed protein of corn, renovated at every collection, made every seven days. These materials were transferred to the Laboratory of Agricultural Entomology of the National Institute for Amazonian Research for sorting, separation by sex and stored in alcohol 80%, for possible identification. The identification was made only with females. A total of 6,665 specimens were collected from IFAM Campus and 1,141 from UFAM Campus. Of this total, six species of Anastrepha were identified in each area of study. In IFAM were found: A. obliqua Macquart (99.17%), A. bahiensis Lima (0.40%), A. distincta Greene (0.13%), A. leptozona Hendel (0.11%), A. striata Schiner (0.15%) and A. antunesi Lima (0.04%). In UFAM were found: A. obliqua Macquart (97.62%), A. bahiensis Lima (1.25%), A. antunesi Lima (0.57%), A. distincta Greene (0.34%), A. serpentina Weidemann (0.11%) and A. turpiniae Stone (0.11%). The bigest Fly trap day in IFAM were in June (6.46), July (3.55), August (1.63) in 2015 and February (3.42), March (2.71) and April (1.21) in 2016. In UFAM the biggest MAD were in July (0.4) and August (0.5) in 2015. A. obliqua was the only dominant, frequent and constant in both cultivated areas. The values of Simpson indices were (0.95 and 0.98), Shannon (0.95 and 0.98) and modified Hill (0.03 and 0.01), for UFAM and IFAM, respectively, indicating low diversity of species. As for the level of fruit infestation the values were (12.13 and 22.15 puparia/fruit) and (151 and 284 puparia/kg). The pupal viability was (84.24% and 97.84%) and the emergency rate (83.85% and 96.95%). These indices of infestation were considered too high. As for the parasitoids, two species were found Doryctobracon areolatus (Szépligeti, 1911) and Oppius bellus (Gahan, 1930). The indices of parasitoid were (0,46% and 0.91%) and were considered low. Considering the plagues of araçá-boi, it was found that only A. obliqua infests the araçá-boi in the crops of Manaus-AM
Keywords: Moscas-das-frutas; Araçá-boi